Mengoptimalkan Hasil Belajar: Pengaruh Efikasi Diri dan Teman Sebaya pada Mahasiswa Universitas Negeri Jakarta - Anita Nur Khoiriyah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to determine and test the Influence of Self-Efficacy and Peer Influence on the Academic Achievement of Students at the State University of Jakarta. This study employs a quantitative research method with descriptive analysis, using a data collection method in the form of questionnaires. The subjects in this research were students from the Jakarta State University, totaling 121 students. This study uses data analysis techniques of the Outer Model with calculations for Convergent Reliability, Discriminant Validity, Composite Reliability, Cronbach's Alpha, and the Inner Model with calculations for T-statistics, R-Square, F-Square, and VIF using SmartPLS 4.0 software. The results of this research indicate that there is a positive and significant influence of self-efficacy on academic achievement with a t-statistic value of 4.124 > 1.96 and a significance value of 0.000 < 0.05. There is also a positive and significant influence of peer influence on academic achievement with a t-statistic value of 5.104 > 1.96 and a significance value of 0.000 < 0.05. The calculated F-Square for the self-efficacy variable on academic achievement is 0.365, and the F-Square for the peer influence variable on academic achievement is 0.173. This indicates that both Self-Efficacy and Peer Group have a positive and significant influence on the Academic Achievement of Students at the State University of Jakarta.